How high-protein, high-fiber meal replacements influence dietary intake in overweight women during weight loss - Muhammad, Harry Freitag Luglio; Nurwanti, Esti; Nurdin, Naufal Muharam (Indonesian Nutrition Association, 2025)
Background and objectives: This study aims to evaluate the effects of high-protein, high-fiber dietary supplements on dietary intake among overweight women.